(untitled) (CIPEEX, 2026)
This expanded summary aims to present the context of the institutionalization of the madness industry, as well as the anti-asylum struggle. It is justified by the reality of asylum practice in Brazil, even years after the country’s redemocratization, which resulted in the enactment of the 1988 Federal Constitution, whose axiomatic axis is respect for and guarantee of human dignity. Despite the pursuit of advances in this area, Resolution No. 487/2023 of the National Council of Justice (CNJ), which instituted the Judiciary’s Anti-Asylum Policy, proves that, unfortunately, the practice of asylums is still present in our country. Therefore, the following problematization arises: What characterizes the madness industry, and what are the challenges in combating it? To this end, the text uses bibliographical research as its method, referencing authors who contributed to the construction of the theme’s significance, as well as to its paradigm shift. The results indicate significant progress in psychiatric reform and mental health policies, although structural challenges remain. Thus, it is concluded that the anti-asylum movement remains fundamental to effectively guaranteeing the rights and social inclusion of people with mental health problems.